2016
DOI: 10.1002/jpln.201600081
|View full text |Cite
|
Sign up to set email alerts
|

Is the photometric method using acetone extracts to determine chlorophyll concentrations applicable to Mg‐deficient plants?

Abstract: A conventional photometric method to determine chlorophyll concentrations in maize leaves was evaluated. It was tested whether in Mg‐deficient plant tissue the addition of MgCO3 during pigment extraction converts protoporphyrin IX into chlorophyll, falsifying concentration measurements. The non‐destructive N‐tester was used as a reference for the destructive chlorophyll determination. It is shown that both methods are valid for the determination of chlorophyll concentration in Mg‐deficient leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Changes in the chlorophyll content of avocado slices are shown in Figure 4a,b. Chlorophyll a (Figure 4a) was the predominant type in fresh-cut avocados, with contents ranging from 22.7 ± 2.1 to 41.05 ± 3.10 mg/kg, whereas chlorophyll b (Figure 4b peroxidase (Jung et al, 2016). However, chlorophyll contents obtained in this study, along with color changes throughout storage (Figure 1a-c), suggest that chlorophyll losses are mainly related to photooxidative reactions occurring during PL treatments.…”
Section: Chlorophylls Contentmentioning
confidence: 58%
See 1 more Smart Citation
“…Changes in the chlorophyll content of avocado slices are shown in Figure 4a,b. Chlorophyll a (Figure 4a) was the predominant type in fresh-cut avocados, with contents ranging from 22.7 ± 2.1 to 41.05 ± 3.10 mg/kg, whereas chlorophyll b (Figure 4b peroxidase (Jung et al, 2016). However, chlorophyll contents obtained in this study, along with color changes throughout storage (Figure 1a-c), suggest that chlorophyll losses are mainly related to photooxidative reactions occurring during PL treatments.…”
Section: Chlorophylls Contentmentioning
confidence: 58%
“…Moreover, a significant (p < .05) decrease in the chlorophyll content of fresh-cut avocados was observed immediately after PL treatments, except in those at UVB-VIS range. The energy applied during PL treatments may cause the breakage of cellular membranes, the loss of cellular compartmentalization(Tao et al, 2019), enhancing the action of hydrolytic enzymes such as chlorophyllase, chlorophyll oxidase, and peroxidase(Jung et al, 2016). However, chlorophyll contents obtained in this study, along with color changes throughout storage (Figure1a-c), suggest that chlorophyll losses are mainly related to photooxidative reactions occurring during PL treatments.Interestingly, results shown that the initial chlorophylls content in PL-treated avocado slices was stable throughout storage, whereas chlorophyll a and b content in untreated avocados decreased by 34% and 44%, respectively, over 12 days.…”
mentioning
confidence: 62%
“…The parameter L* represents the lightness index, a* represents redness or greenness, and b* represents yellowness or blueness . The chlorophyll (Chl) concentration was determined as previously described …”
Section: Methodsmentioning
confidence: 99%
“…53 The chlorophyll (Chl) concentration was determined as previously described. 54 Measurement of Total Anthocyanin Content. Anthocyanins were extracted as previously described 19 with minor modifications.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…After stripping the shell, 10-20 dry grains were ground, after which 0.8-1 g powdered material was treated with 80% (v/v) acetone under shade conditions. The Chl content was quantified using a published method (Jung et al, 2016). Three technical replicates were used to calculate the standard deviation.…”
Section: Measurement Of Chlorophyll Contentmentioning
confidence: 99%